2013
DOI: 10.2298/abs1303945g
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of white spot syndrome virus on wild and farm crustaceans from Sonora, Mexico

Abstract: White spot syndrome is a viral disease affecting wild and farm crustaceans that serve as reservoirs. Previous reports have demonstrated high genomic variation in WSS viruses (WSSV) isolated from distinct geographical regions. In this study, we collected wild shrimps (Litopenaeus stylirostris), crabs (Callinectes arcuatus) and farmed shrimp (L. vannamei) in Sonora, Mexico, between 2008 and 2010. DNA was extracted, and the variable regions and transposase genes were subjected to PCR and sequencing. Compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…This could indicate that this haplotype was generated in -or entered -the northwestern region of Mexico from the north and spread southward (Table S1). The presence of the 3-RU haplotypes has been reported in India and Sonora, Mexico, previously, but this is the first report of the distribution of SNPs at Position 48 of RUs in America; therefore, it is possible that they have the same haplotype described here, though this was not reported (Pradeep et al 2008, Gonzalez-Galaviz et al 2013. Simrouni et al (2014) reported 2 variants of ORF 94 with 3 RUs isolated in Iran in 2012 that have different patterns from those reported in this work, as they found SNP patterns G,G,G and T,T,T.…”
Section: Orf 94mentioning
confidence: 43%
See 1 more Smart Citation
“…This could indicate that this haplotype was generated in -or entered -the northwestern region of Mexico from the north and spread southward (Table S1). The presence of the 3-RU haplotypes has been reported in India and Sonora, Mexico, previously, but this is the first report of the distribution of SNPs at Position 48 of RUs in America; therefore, it is possible that they have the same haplotype described here, though this was not reported (Pradeep et al 2008, Gonzalez-Galaviz et al 2013. Simrouni et al (2014) reported 2 variants of ORF 94 with 3 RUs isolated in Iran in 2012 that have different patterns from those reported in this work, as they found SNP patterns G,G,G and T,T,T.…”
Section: Orf 94mentioning
confidence: 43%
“…Most of the epidemiological studies performed with WSSV and these 3 markers are based only on the size of the mini-satellite and are expressed as the number of RUs (Dieu et al 2004, Pradeep et al 2008, Dieu et al 2010, Tan & Shi 2011, Shekar et al 2012, and Mexico is no exception (Galaviz-Silva et al 2009, Gonzalez-Galaviz et al 2013. However, each RU may contain SNPs that are useful for differentiating haplotypes that have the same number of RUs.…”
Section: Introductionmentioning
confidence: 99%
“…The present report is based on three minisatellites ORF 75, 94 and 125. Application of these methods for typing WSSV isolates has been reported widely from the shrimp growing countries in the world (Dieu et al, 2004;Hoa et al, 2012;Gonzalez-Galaviz et al, 2013) while similar studies are limited from India (Musthaq et al, 2006;Pradeep et al, 2008;John et al, 2010) and the present study is the first report of WSSV genotyping from the state of Gujarat.…”
mentioning
confidence: 72%
“…These variables loci have been considered as important molecular markers for WSSV genotyping. The single nucleotide mutations, including deletions, insertions, and single nucleotide polymorphisms (SNP) have been suggested as markers for genetic diversity studies of WSSV (John et al, 2010;Hoa et al, 2011;González-Galaviz et al, 2013).…”
mentioning
confidence: 99%
“…This region shows more variation, with a wide range of compound repeat units (RUs) between the WSSV isolates originating from farming and wild hosts (Wongteerasupaya et al, 2003;Dieu et al, 2004;Musthaq et al, 2006;Pradeep et al, 2008;John et al, 2010;González-Galaviz et al, 2013). Several studies have suggested a correlation between the RUs of ORF94 and WSSV virulence as follows: the fewer RUs (<9) the higher mortality rate in shrimps (Waikhom et al, 2006;Pradeep et al, 2008;Hoa et al, 2012).…”
mentioning
confidence: 99%